2018
DOI: 10.1002/pros.23690
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pelvic pain and prostate inflammation in rat experimental autoimmune prostatitis: Effect of a single treatment with phosphodiesterase 5 inhibitors on chronic pelvic pain

Abstract: Prostatitis leads to inflammatory changes in the prostate, which may contribute to the development and maintenance of chronic pelvic pain. PDE5 inhibitors, including tadalafil, may have the ability to block chronic pelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…Six to eight-week-old male NOD mice were intradermally immunized in different locations: bilateral hint footpads, the lower back, and the base of the tail with PAgs (300 μg/mouse, EAP group) or phosphate buffer solution (control group) emulsified in CFA in a total volume of 150 μL per mouse, as previously described. 24 According to the experimental schedule, 25,26 the mice were immunized at day 0 and day 28 and at last were killed at day 42.…”
Section: Eap Inductionmentioning
confidence: 99%
“…Six to eight-week-old male NOD mice were intradermally immunized in different locations: bilateral hint footpads, the lower back, and the base of the tail with PAgs (300 μg/mouse, EAP group) or phosphate buffer solution (control group) emulsified in CFA in a total volume of 150 μL per mouse, as previously described. 24 According to the experimental schedule, 25,26 the mice were immunized at day 0 and day 28 and at last were killed at day 42.…”
Section: Eap Inductionmentioning
confidence: 99%
“…Our recent study (Kurita et al) showed that even a single oral dose of tadalafil or other PDE5 inhibitors (sildenafil and vardenafil) inhibited EAP‐induced chronic pelvic pain. However, in the present study, we did not administer tadalafil to the rats on the last day of the experimental schedule, when the rats were sacrificed in both models.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have focused on the effect of tadalafil on chronic prostatitis symptoms in patients with CP/CPPS, although PDE5 inhibitors including tadalafil have been reported to suppress prostate inflammation, fibrosis, and hypo-oxygenation in rabbits fed a high fat diet and to suppress pelvic pain by improving inflammatory changes in an experimental autoimmune prostatitis rat model. 13,14,18,19 In clinical practice, Benelli et al 20 reported that tadalafil significantly improved the NIH-CPSI total score, as well as scores for the pain domain, urinary domain, and QOL domain in 14 patients with CP/CPPS, although they found that the Qmax and PVR in UFM did not improve. In particular, the mean NIH-CPSI pain sub-score decreased from 13.7 to 1.6 after 12 weeks of tadalafil administration, and this change is considered to be noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several basic studies have reported that tadalafil significantly suppressed pelvic pain and prostatic inflammation in a nonbacterial prostatitis rat model. 13,14 It is of clinical interest to determine whether these old and new drugs, cernitin and tadalafil, respectively, can improve chronic pain or discomfort of the pelvic, perineal, scrotal, or phallic area in patients with CP/CPPS. To the best of our knowledge, no randomized controlled studies have compared the improvement in chronic prostatitis symptoms, such as chronic pelvic pain, in patients treated with one of these medications.…”
Section: Introductionmentioning
confidence: 99%